Development of the Treatment Attitudes Questionnaire in Bipolar Disorder - Johnson, Sheri L. (2008)
Despite the success of pharmacotherapy in the management of bipolar disorder, as many as one-half of those in treatment discontinue their medication over time. Currently, no self-report measure is available that predicts treatment engagement in bipolar disorder. The goal of the current study was to develop a measure of awareness of symptoms and attitudes toward treatment among those with bipolar disorder. Sixty-six participants diagnosed with bipolar I disorder on the SCID completed the Treatment Attitudes Questionnaire (TAQ) and were then followed for up to 2 years to assess symptom levels. Medication data were available for 37 participants. Analyses of the TAQ were conducted to examine reliability, predictors of subscales, and how well scores predicted medication and symptom levels over time. Results indicate that previous episodes of depression, but not episodes of mania, correlated with increased scores on the Insight and the Enjoyment of Mania subscales. Scores on the Nonbiological Attributions subscale predicted lower levels of lithium as well as increased depressive symptoms over time. Although the current study includes limited measurement of treatment engagement and a small sample size, this easily administered scale may help treatment planning for those with bipolar disorder.